ANALISIS KEMAMPUAN NUMERASI SISWA PADA MATERI BANGUN DATAR KELAS 1 SDN MERJOSARI 4 - Amira Cayyisa Abyda Elfauzy; Umi Khusmiyatun; Nuzula Hidayatul Khusna; Wahyuni Hidayati; Alus Marwandi Kusuma; Beti Istanti Suwandayani (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to analyze the numeracy skills of first-grade students at SDN Merjosari 4 in flat shape material and identify factors that influence students' understanding of geometric concepts. This study uses a qualitative approach with a descriptive method, involving three data collection techniques: interviews, observation, and documentation. The research subjects consisted of first-grade mathematics teachers and 20 students who attended classes in that grade. The results showed that the majority of students (12 students) were in the high numeracy category, while 5 students were in the medium category and 3 students were in the low category. Teachers have implemented various learning strategies in line with students' cognitive development, such as the use of concrete media (e.g., folded paper, rubber bands, and videos) and contextual learning models that relate the material to students' daily lives. However, there are still some students who have difficulty understanding flat shape concepts, which is influenced by low learning motivation and lack of parental support. This study suggests the need for more personalized and tiered learning interventions, as well as the use of various types of representations to help all students achieve optimal numeracy development. These findings also underscore the importance of using concrete media and contextual approaches in mathematics learning, especially at the early childhood cognitive development stage.